Colorectal Carcinogenic Pathways and Chemotherapeutic Responsiveness : A Review - Harrison, Sanjay; Benziger, Harrison (Journal of Digestive Disorders And Diagnosis, 2017)
This review synthesizes key molecular pathways in colorectal carcinogenesis and relates them to differential chemotherapeutic responsiveness. It discusses mismatch repair, chromosomal instability, and serrated pathways, linking biomarkers to therapeutic decision‑making.
Keywords: Colorectal neoplasms; microsatellite instability; chromosomal instability; antibodies monoclonal; chemotherapy adjuvant